Synthesis and Antibacterial Activity of Thienopyrimidine Amide Derivatives - Tharikoppula, Giri; Eppakayala, Laxminarayana; Maringanti, Thirumala Chary; Kamalapuram, Chiranjeevi; Kudle, Karunakar Rao (Asian Journal of Chemistry, 2017)
Thienopyrimidine amide derivatives are important class of organic compounds and show wide range of biological activity. Hence the researchers are paying more attention towards the synthesis of these compounds. A series of thienopyrimidine amide derivatives (13a-m) was synthesized. The newly synthesized amide derivatives (13a-m) were characterized by 1H NMR, 13C NMR, Mass and IR spectral data. Further these compounds were evaluated for their antibacterial activity.